2007
DOI: 10.1080/14616730701455395
|View full text |Cite
|
Sign up to set email alerts
|

Depressed and healthy preschoolers' internal representations of their mothers' caregiving: Associations with observed caregiving behaviors one year later

Abstract: This study examined diagnostic group differences in children's internal representations of their mothers and mothers' parenting strategies 1 year later. Mother -preschool child dyads (N = 279) were examined. The sample included 151 healthy, 75 depressed, and 53 disruptive disordered preschoolers. The MacArthur Story Stem Battery (MSSB) was administered at baseline. One year later, mothers' caregiving strategies were measured. Results indicated that higher depression severity was associated with preschoolers' g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…Despite many studies showing associations between maternal sensitivity and child attachment [3] and, in turn, between attachment and subsequent or concurrent representations [9,10], only a few studies have documented the link between quality of mother-child interactions and children's attachment representations [11][12][13]. Overall, these findings are consistent with the claim that preschoolers internalize their caregiving relationships and that these representations are reflected by the content of their narratives.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite many studies showing associations between maternal sensitivity and child attachment [3] and, in turn, between attachment and subsequent or concurrent representations [9,10], only a few studies have documented the link between quality of mother-child interactions and children's attachment representations [11][12][13]. Overall, these findings are consistent with the claim that preschoolers internalize their caregiving relationships and that these representations are reflected by the content of their narratives.…”
Section: Introductionsupporting
confidence: 86%
“…Moreover, because the majority of studies on the sensitivity-attachment representation link have been conducted on high-risk [11,13] or clinical samples [12], generalization to low-risk dyads is also problematic. The present study is aimed at exploring associations between maternal interactive behaviour and children's attachment representations as assessed via a story stem procedure in a population including both preterm and full-term infants.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that there are preschoolers who have ongoing, severe behavioral disorders consisting of dangerous aggression, impulsivity, and unmanageability in the home [23], which is congruent with literature indicating that the highest risk children tend to display high levels of aggression coupled with negative patterns of parenting and family stress [24]. Additionally, preschoolers have been shown to evidence clear criteria for depression that are stable over time and are associated with functional impairment, a positive family history for mood disorder, early environmental stress, negative parentchild interactions, and negative internalizations of the caregiver [25][26][27][28].…”
Section: Introductionsupporting
confidence: 68%
“…Thus, each parent's supportive caregiving score represents the total number of supportive behaviors they were observed using over the course of the 8-min task. Prior findings suggest that caregiving support behaviors coded during this task have good psychometric properties (29,30). Specifically, Cronbach's alpha for the combined supportive behaviors coded was alpha = 0.86.…”
Section: Methodsmentioning
confidence: 98%